Indigenous amazonic; movement & collective action in enviramental conflicts: the cases of ‘Amarakaeri’ reserve and ‘Curaray’ river basin - Gamboa Balbín, Aída Mercedes (2013)
Through  the  cases  of  ‘La  Reserva  ComunalAmarakaeri’ and ‘La Cuenca del Río Curaray’ we argue that the success of indigenous collective action in environmental conflicts generated  by the superposition of hydrocarbon blocks on titled indigenous lands and protected areas is defined by1) a regional system more open to the indigenous movement that allows alliances within the regional elite, 2) organizational forms providing specific strategies that integrate dialogue practices and a broad network of partners cohesive to targets, 3) the use of an ideological discourse that uses collective rights and demands for inclusion in order to generate union within the collective and the sensibilization of the authorities. On the other hand, failure is caused by 1) the absence of alliances in the regional elite and the presence of repressive authorities, 2) weak complex organizational forms that use ineffective strategies and models of mobilization without dialogue, 3) a discourse that does not integrates the collective rights with demands for equality, creating fragmentation in the organization and a fragile impact on the authorities.